APPLICATIONS LIQUID ORGANIC FERTILIZER AND COMPOSITION OF PLANT MEDIA TO RESULT OF SELADA PLANTS (Lactuca sativa L) - Sri Hidayati (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2017)
Abstract: Lettuce (lactuca sativa) is a vegetable that has a very high economic value. Where this plant can be grown in temperate and tropical regions, Lettuce production is still low, then this plant needs to be given fertilizer treatment. One of the fertilizer that can be used is liquid organic fertilizer. Liquid Organic Fertilizer has several benefits such as to encourage and increase the growth and yield of plants. Objective: To know the effect of combination of planting media composition and liquid organic fertilizer to growth and yield of lettuce crop; To know the influence of plant plant composition on growth and yield of lettuce plant; To know the effect of liquid organic fertilizer on growth and yield of lettuce plant. The experiment was conducted in experimental garden of Faculty of Agriculture Universitas Merdeka Surabaya Jl.Ketintang Madya VII / 2 Surabaya, with the space 0-20 meters above sea level. This research is a pot experiment and is a two factor factorial research with Randomized Block Design (RAK), the first factor is Liquid Organic Fertilizer with 3 levels and the second factor is the composition of planting media with 4 levels. Where Factor I: liquid organic fertilizer consisting of: P1: 1 ml / plant; P2: 2 ml / plant; P3: 3 ml / plant, Factor II: planting medium consisting of 4 (four) levels, namely: M1: soil + manure + rice husk: 2: 1: 1; M2: soil + manure + rice husk: 1: 1: 1; M3: ground + manure + sand: 2: 1: 1; M4: ground + manure + sand: 1: 1: 1, treatment repeated 3 times and each treatment there are 2 plant samples, so the number of plants as much 72 or 72 polybag.Based on the results of research conducted, it can be concluded as follows:1. POC concentration factor (P) showed significant influence on all variables studied such as leaf number, plant length and wet weight of plant.2. The media composition factor (M) showed a nonsignificant effect on all variables studied such as leaf number, plant length and wet weight of the plant.3. There was significant interaction in combination of treatment between Liquid organic (P) and media composition factor (M) and to plant length variables. At age 35 days after planting. The highest value obtained P2M2 of 14.00 and the lowest value obtained by 11.83. Keywords: Lettuce Plants, Liquid Organic Fertilizer, Planting Media